Pengembangan Sumber Daya Manusia untuk Meningkatkan Kinerja Kewirausahaan Berdasarkan Kearifan Lokal di Pesantren - Irwan Candra; Rukin Rukin; Heri Sudarsono (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
Pesantren, as an Islamic educational institution that has long been a center of religious learning and character development, has great potential in advancing entrepreneurship based on local wisdom. The role of pesantren is not only limited to teaching religious studies, but also includes coaching students to have economic independence and competitiveness in the midst of the Times. Local wisdom that grows around pesantren can be an important capital in developing businesses that are relevant to the needs of the community. However, optimizing the function of pesantren in producing students who are independent and able to compete still faces various challenges. One of the main obstacles is the development of Human Resources (HR) which is not only oriented to mastering the theory, but also on practical skills and understanding of local values. Without the right strategy, such great potential is difficult to realize sustainably. This study aims to explore strategies that can be applied in the development of human resources in order to improve the performance of local wisdom-based entrepreneurship in the boarding school. The research method used is a qualitative approach with case studies on several boarding schools that have succeeded in forming productive business units by utilizing local potential, such as agriculture, fisheries, crafts, and food product processing. Research findings indicate that several crucial factors in building entrepreneurial human resources in pesantren include: strengthening character and work ethic, hands-on practice-based training in the field, collaboration with local business actors for knowledge transfer and market networking, as well as historical and philosophical understanding of local wisdom values. The success of entrepreneurship development in pesantren depends on the integration of spiritual aspects, practical skills, and knowledge about the potential of the region. Based on the results of the study, an integrated entrepreneurship training model that combines science, faith, and concrete action is recommended. This Model is expected to produce great pesantren entrepreneurs, competitive, and able to adapt and face global challenges without leaving their identity and noble values.